Endogenous retrovirus group FRD member 1 is a potential biomarker for prognosis and immunotherapy for kidney renal clear cell carcinoma - Wen, Xiaofen; Shen, Jiaxin; De Miglio, Maria Rosaria; Zeng, De; Sechi, Leonardo A. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The activation of endogenous retroviral (ERV) genes in kidney renal clear cell carcinoma (KIRC) suggests the necessity for further research on their functions. Methods In this study, KIRC and healthy cohorts were obtained from TGGA and GEO datasets. Subsequently, differential analysis and functional annotation were conducted using GO, KEGG, and GSEA. Clinical outcomes were then observed and utilized in the development of a nomogram. Results We observed the general low expression of ERVFRD-1 in KIRC tumors compared to normal tissue (P < 0.001) across multiple cohorts. Differential analysis and functional annotation using GO, KEGG, GSEA analysis revealed significant involvement of ERVFRD-1 in tumor immunoregulation: a close relation to the infiltration levels of mast cells and Treg cell (P < 0.001) and occurrence with a variety of immune markers. Methylation status was then applied to uncover potential mechanisms of ERVFRD-1 in KIRC. Notably, higher expression levels of ERVFRD-1 were associated with extended overall survival, disease-specific survival, and progression-free survival. Finally, based on Cox regression analysis, we constructed a nomogram incorporating ERVFRD-1, pathologic T, and age, which exhibited promising predictive power in assessing the survival outcomes of KIRC patients. Discussion To sum up, our study suggests that ERVFRD-1 plays a role in regulating immunological activity within the tumor microenvironment and is associated with overall survival in KIRC patients. ERVFRD-1 may therefore be a sensitive biomarker for diagnosis, immunotherapy, and prognosis assessment of KIRC.